2016
DOI: 10.1200/jop.2016.011809
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Strategies for Patients With Metastatic Renal Cell Carcinoma in Whom First-Line Vascular Endothelial Growth Factor Receptor–Directed Therapies Fail

Abstract: Metastases are present in one third of renal cell carcinomas at diagnosis. The overall survival duration in metastatic renal cell carcinoma is approximately 22 months, which underlines the need for more effective systemic treatments. Therapies on the basis of antiangiogenic agents and inhibitors of the mammalian target of rapamycin have been approved for treatment of metastatic renal cell carcinoma, but only benefits for progression-free survival were demonstrated in the second-line setting. Fortunately, promi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 68 publications
(66 reference statements)
0
9
0
1
Order By: Relevance
“…These pathways are associated with key angiogenesis events that include cell proliferation, migration, survival, and vascular permeability (Roskoski, 2017). In patients with ccRCC being treated with VEGF and mTOR blockers, angiogenesis can be stimulated by angiopoietin 2, c-MET, or interleukin (Malouf et al, 2016).…”
Section: Molecular Mechanisms In Hypoxia and Angiogenesis In Ccrcc: Tmentioning
confidence: 99%
“…These pathways are associated with key angiogenesis events that include cell proliferation, migration, survival, and vascular permeability (Roskoski, 2017). In patients with ccRCC being treated with VEGF and mTOR blockers, angiogenesis can be stimulated by angiopoietin 2, c-MET, or interleukin (Malouf et al, 2016).…”
Section: Molecular Mechanisms In Hypoxia and Angiogenesis In Ccrcc: Tmentioning
confidence: 99%
“…Retrospective data showed that in patients previously treated with nivolumab, TKIs remain active in subsequent lines of treatment, which supports the use of cabozantinib after immune checkpoint inhibitors [Albiges et al 2015;Malouf et al 2016]. Currently we lack biomarkers in advanced RCC or mRCC to select the best treatment option for patients and we base our treatment selection on a patient's relative contraindications to certain therapy, the results of clinical trials, and subgroup analyses to guide the therapy decision.…”
Section: Cabozantinib In the Third-line Settingmentioning
confidence: 99%
“…Clinical trials to evaluate such specific subpopulations need further evaluation. Finally, the approval of the immune checkpoint inhibitor nivolumab as second line in mC-CRCC treatment also introduces complexity in the choice of the best sequence (Malouf et al, 2016).…”
Section: Choice Of Pki For Mccrccmentioning
confidence: 99%